High-entropy high-nickel single crystal lithium ion battery positive electrode material and preparation method thereof

By using high-entropy high-nickel single crystal morphology and high-entropy alloy doping methods in the positive electrode materials of lithium-ion batteries, the cation mixing and lattice defects of high-nickel positive electrode materials are solved, and the electrochemistry of the material is significantly improved Performance and security.

CN119495740AActive Publication Date: 2025-02-21UNIV OF ELECTRONICS SCI & TECH OF CHINA

Patent Information

Application Number
CN202411682564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-21
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The high-nickel nickel-cobalt lithium manganate positive electrode material has problems such as cation mixing, lattice defects, grain boundary cracks, and surface residual lithium compounds, resulting in short material life, poor safety and low energy density.

Method used

The positive electrode material of high-entropy high-nickel single-crystal lithium-ion battery was used to synthesize the single crystal morphology of high-entropy high-nickel material through the high-temperature solid phase method, and combined with high-entropy alloy doping, a uniformly distributed layered structure single-crystal particle material was formed.

Benefits of technology

It achieves high mechanical strength, low specific surface area, and low defect density of the material, and improves electrochemical performance, including good safety performance, long cycle life, high voltage resistance, large compaction density and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495740A_ABST
    Figure CN119495740A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, provides a high-entropy high-nickel single crystal lithium ion battery positive electrode material and a preparation method thereof, and aims to solve many problems of a high-nickel nickel cobalt lithium manganate positive electrode material and improve the comprehensive performance of the high-nickel nickel cobalt lithium manganate positive electrode material. Aiming at the modification requirement of the high-nickel layered nickel cobalt lithium manganate ternary system positive electrode material, a high-entropy alloy doping strategy is provided on the basis of a combination design and a component proportion design, and meanwhile, the strict design of a preparation process is combined on the basis of high-entropy alloy doping, so that the positive electrode material after high-entropy doping presents a single-crystal morphology, and the high-entropy doping performance of the positive electrode material is improved. The specific molecular expression is Li < 1 + delta > [Ni < 0.86 + / -x > Co < 0.04 + / -x / 2 > Mn < 0.1 + / -x / 2 > (OH) < 2 >] < 1-z > MzO2, delta is greater than or equal to 0 and less than or equal to 0.2, x is greater than or equal to 0 and less than or equal to 0.06, and z is greater than or equal to 0.005 and less than or equal to 0.25; m is at least five of Al, Mg, Ti, Zr, Ga, In, Y, La, B, Si and Nb. In conclusion, the high-entropy and high-nickel positive electrode material with the single crystal morphology is synthesized by adopting a high-temperature solid-phase method, and the positive electrode material shows good electrochemical performance and can show relatively good specific discharge capacity and cycling stability under the high voltage of 2.8-4.5 V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, relates to positive electrode materials for lithium ion batteries, and specifically provides a high-entropy high-nickel single crystal lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of industrial technology, people's demand for energy is increasing, and with it comes an increasingly serious fossil energy crisis and the corresponding environmental pollution problems; therefore, in recent years, the demand for the research and development of new energy has been increasing. Among many new energy technology industries, lithium-ion batteries (LIBs) stand out due to their excellent characteristics such as high energy density and high cycle stability. As a secondary battery, lithium-ion batteries have many significant advantages and have become the dual focus of scientific research and industrialization; in addition, lithium-ion batteries also have the advantages of being green, environmentally friendly and pollution-free, so they are widely used in portable electronic devices, new energy vehicles, medical equipment and other fields; at the same time, this also means that people have higher and higher requirements for the performance of lithium-ion batteries.

[0003] At present, among the commonly used positive electrode materials for lithium-ion batteries, high-nickel layered nickel-cobalt-manganese ternary positive electrode materials (NCM) are widely used. This material is a layered structure material with a chemical formula of LiNi x Co y Mn z O2 (x ≥ 0.6), usually presents an α-NaFeO2 type layered structure, belongs to the hexagonal system, R-3m space group; NCM is modified by combining LiCoO2, LiNiO2 and LiMnO2, and combines the excellent properties of these three materials, including the high capacity of lithium nickel oxide, the excellent stability of lithium cobalt oxide, and the high thermal stability of lithium manganese oxide, showing excellent electrochemical performance, with a capacity of up to 274mAh g -1 Theoretical specific capacity and average working voltage of 3.6V. However, high-nickel nickel cobalt manganese oxide positive electrode materials are usually composed of numerous tiny primary particles that are agglomerated to form secondary composite polycrystalline particles. Under this structure, Li + It will continuously embed and eject itself from the material's internal lattice, which will trigger a series of structural changes and phase transitions in the long run. In addition, this ternary material also faces problems such as cation mixing, lattice defects, grain boundary cracks, and residual lithium compounds on the surface. These problems will have a huge impact on performance, resulting in short material life and poor safety. Moreover, due to its inability to withstand high-voltage charging, the material's energy density is also low, which greatly limits the material's further development and application.

[0004] In view of the series of problems existing in the above-mentioned layered nickel-cobalt-manganese ternary cathode materials, various modification studies have been conducted, including but not limited to doping and coating, but the overall performance after modification is still unsatisfactory. Therefore, combining multiple modification methods to improve the performance of lithium-ion batteries has become an important issue for the large-scale application of commercial lithium-ion batteries. It is urgent to propose better and newer solutions to overcome the problems faced by high-nickel cathode materials and improve their overall performance. Summary of the invention

[0005] The purpose of the present invention is to provide a high-entropy high-nickel single crystal lithium ion battery positive electrode material and a preparation method thereof, so as to solve the problems of cation mixing, lattice defects, grain boundary cracks, residual lithium compounds on the surface, etc. in high-nickel nickel cobalt manganese oxide positive electrode materials, improve their comprehensive performances such as poor safety, short life, inability to withstand high voltage charging and low energy density, thereby improving the comprehensive electrochemical performance of lithium ion batteries. Aiming at the modification requirements of high-nickel layered nickel cobalt manganese ternary positive electrode materials, the present invention proposes high entropy alloy doping based on combination design and component ratio modulation design, and at the same time, on the basis of high entropy alloy doping, combined with the strict design of the preparation process, the positive electrode material after high entropy doping presents a single crystal morphology; the single crystal morphology makes the positive electrode material show a very high compaction density, has the advantages of high mechanical strength, low specific surface area, and low defect density, and is also better in electrochemical performance, such as good safety performance, long cycle life, resistance to high voltage charging, large compaction density and high energy density. In addition, the single crystal morphology also reduces the accumulation of internal stress, making the removal and embedding of lithium ions smoother, showing better reversibility and higher energy density; and for the positive electrode material after high entropy doping, the high entropy alloy exists in the form of a solid solution inside the material. This large configuration entropy makes the material have better stability, showing excellent cycle stability and longer working life. The present invention creatively realizes the effective combination of the above two modification methods, and adopts a high-temperature solid-phase method to synthesize a single crystal morphology of high-entropy high-nickel lithium-ion battery positive electrode material, so that it exhibits good electrochemical properties, and can show good specific capacity and stability at a high cut-off voltage of 2.8 to 4.5V; and the high-temperature solid-phase method is simple in process, easy to achieve precise control, and suitable for large-scale industrial production.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, characterized in that the lithium-ion battery positive electrode material is a single crystal morphology, and the molecular expression is:

[0008] Li 1+δ [Ni 0.86±x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2] 1-z M zO2,

[0009] Among them, 0≤δ≤0.2, 0≤x≤0.06, 0.005≤z≤0.25;

[0010] M is at least five of Al, Mg, Ti, Zr, Ga, In, Y, La, B, Si, and Nb;

[0011] In particular: M=[Al+Ga+Ti+Y+Zr], [Al+In+Ti+Y+Zr], [La+Ga+Ti+Y+Zr] or [La+In+Ti+Y+Zr], and the molar ratio of (Al or La):(Ga or In):Ti:Y:Zr is 2:1:1:1:1.

[0012] Furthermore, the method for preparing the high entropy high nickel single crystal lithium ion battery positive electrode material is characterized by comprising the following steps:

[0013] S1. Grind the lithium source (lithium hydroxide) and mix it with the precursor and the doping material to obtain a mixed raw material;

[0014] S2. The mixed raw material is placed in a tubular furnace, heated to 450 ℃ ~ 600 ℃ at a heating rate of 2 to 5 ℃ / min in an oxygen atmosphere, and kept warm for 4 to 8 hours to obtain a pre-sintered material after pre-sintering;

[0015] S3. Grind the pre-burned material evenly to obtain a pre-burned powder;

[0016] S4. Place the pre-burned powder in a tubular furnace, heat it to 750°C to 950°C at a heating rate of 2 to 5°C / min in an oxygen atmosphere, and keep it warm for 12 to 24 hours. After sintering, a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material is obtained.

[0017] Furthermore, in step S1, the molar ratio of lithium hydroxide, precursor, and doping material is: (1+δ):(1-z):z, 0≤δ≤0.2, 0.005≤z≤0.25.

[0018] Furthermore, in step S1, the precursor material uses an 8-series ternary precursor, and the chemical formula is: Ni 0.86± x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2, 0≤x≤0.06; typical composition is [Ni 0.86 Co 0.04 Mn 0.1 (OH)2].

[0019] Furthermore, in step S1, the doping material M is at least five oxides or hydroxides of Al, Mg, Ti, Zr, Ga, In, Y, La, B, Si, and Nb, and the specific typical combinations of doping materials are [Al+Ga+Ti+Y+Zr], [Al+In+Ti+Y+Zr], [La+Ga+Ti+Y+Zr] or [La+In+Ti+Y+Zr], and the molar ratio of (Al or La):(Ga or In):Ti:Y:Zr is 2:1:1:1:1.

[0020] Based on the above technical solution, the beneficial effects of the present invention are:

[0021] The present invention proposes a high-entropy high-nickel single crystal lithium-ion battery positive electrode material and a preparation method thereof, creatively realizing the effective combination of single crystal morphology and high entropy doping, and preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material by a high-temperature solid phase method, which has a high reversible specific capacity and cycle stability. By adopting a high-temperature solid phase method, the lithium source, the precursor and the doping raw material are mixed, pre-burned, ground, sintered and other steps, and the process conditions of the preparation process are strictly controlled to obtain a high-entropy positive electrode material with a single crystal morphology, forming a uniformly distributed layered structure single crystal granular material. This structural material can better overcome the defects such as lattice defects and grain boundary cracks faced by traditional polycrystalline materials, and high entropy doping can more finely control the configuration of the material, effectively suppress the cation mixing under the joint action of multiple elements, and increase the Li + The diffusion channel gives the material excellent cycle performance and structural stability.

[0022] In summary, the high-entropy high-nickel single crystal lithium-ion battery cathode material proposed in the present invention can achieve a capacity of 181.0 mAh g during the charge and discharge process at a 0.5C rate. -1 After 100 cycles, the capacity retention rate is 86.4%; and it also shows good specific capacity and stability at a high cut-off voltage of 2.8-4.5V, with a specific capacity of 191.8mAh·g at a rate of 0.5C. -1 After 100 cycles, the specific capacity is 149.3 mAh g -1 The capacity retention rate is 79.1%, which is 147.8 mAh g at 2.8-4.3 V. -1 The results are almost completely consistent, proving that the material is fully capable of working under higher cut-off voltages and has the ability to withstand high-voltage charging; moreover, the preparation process of the high-entropy, high-nickel single crystal lithium-ion battery positive electrode material proposed in the present invention is easy to control, the process flow is very simple and can be precisely controlled, it has very good application prospects, and is expected to be put into large-scale industrial production processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1The present invention is a flow chart of the preparation process of the high-entropy high-nickel single crystal lithium-ion battery positive electrode material.

[0024] Figure 2 This is the XRD diagram of the high entropy, high nickel single crystal lithium ion battery positive electrode material in Example 1 of the present invention.

[0025] Figure 3 This is a SEM image of the high entropy, high nickel single crystal lithium ion battery positive electrode material in Example 1 of the present invention.

[0026] Figure 4 This is a first cycle charge and discharge curve of the high entropy high nickel single crystal lithium ion battery positive electrode material at a 0.5C rate in Example 1 of the present invention.

[0027] Figure 5 This is a cycle performance curve of the high entropy, high nickel single crystal lithium ion battery positive electrode material at a 0.5C rate according to Example 1 of the present invention.

[0028] Figure 6 This is a cycle performance curve of the high entropy, high nickel single crystal lithium ion battery positive electrode material of Example 1 of the present invention at an operating voltage of 2.8 to 4.5 V at a 0.5C rate. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0030] Example 1

[0031] This embodiment provides a high entropy high nickel single crystal lithium ion battery positive electrode material. The lithium ion battery positive electrode material is a single crystal morphology, and the molecular expression is: Li 1+δ [Ni 0.86±x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2] 1-z M z O2, δ=0.05, x=0, z=0.03, M=[Al+Ga+Ti+Y+Zr].

[0032] The preparation process of the high entropy high nickel single crystal lithium ion battery positive electrode material is as follows: Figure 1 As shown, using 8 series ternary precursor, lithium hydroxide and dopant as raw materials, the specific steps include:

[0033] S1. Use an electronic analytical balance to accurately weigh the following raw and auxiliary materials: lithium hydroxide, [Ni 0.86±x Co 0.04±x / 2Mn 0.1±x / 2 (OH)2] precursor (typical composition is [Ni 0.86 Co 0.04 Mn0.1 (OH)2]), aluminum hydroxide, gallium oxide, titanium oxide, yttrium oxide, zirconium oxide, among which LiOH: precursor: Al 3+ :Ga 2+ :Ti 4+ : Y 3+ :Zr 4+ The molar ratio is 1.05:0.97:0.01:0.005:0.005:0.005:0.005;

[0034] In an agate mortar, lithium hydroxide is carefully ground into uniform fine powder particles, and then the precursor and doping materials (aluminum hydroxide, gallium oxide, titanium oxide, yttrium oxide, zirconium oxide) are added and repeatedly stirred until the mixture is uniform to obtain a mixed raw material;

[0035] S2. The mixed raw material was loaded into a porcelain boat and placed in a tube furnace, an oxygen atmosphere was introduced, the temperature was raised to 500°C at a heating rate of 5°C / min, and the mixture was kept for 5 hours to complete the pre-sintering to obtain a pre-sintered material;

[0036] S3. The pre-burned material was removed and carefully ground into uniform fine powder particles in an agate mortar to obtain a pre-burned powder;

[0037] S4. The pre-fired powder is loaded into a porcelain boat and placed in a tubular furnace. An oxygen atmosphere is introduced and the temperature is increased to 800°C at a heating rate of 5°C / min. The temperature is kept for 12 hours to complete sintering to obtain a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material.

[0038] The beneficial effects of the present invention are described in detail below in conjunction with tests:

[0039] First, X-ray diffraction (XRD) was used to characterize the structure of the material with a scanning range of 5° to 90° and a scanning rate of 2° min -1 , the results are as follows Figure 2 As shown in the figure, all the characteristic peaks correspond to the layered hexagonal α-NaFeO2 structure of the R-3m space group, and the splitting of the two groups of peaks (006) / (102) and (108) / (110) is very obvious, indicating that the material maintains a highly ordered layered structure and low cation mixing;

[0040] Then, the material was characterized by scanning electron microscopy (SEM) to observe its morphology. Figure 3 As shown in the figure, it can be seen that the material forms irregular polyhedral grains, which is a typical single crystal morphology;

[0041] Finally, the electrochemical performance test of the positive electrode material is carried out. The specific process of the electrochemical performance test is as follows:

[0042] The high-entropy high-nickel single crystal lithium-ion battery positive electrode material was mixed with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride, PVDF) in a mass ratio of 85:10:5, and fully ground in an agate mortar to obtain a slurry; the slurry was evenly coated on the surface of a clean aluminum foil using a scraper to form a 150um coating layer, which was placed in an oven at 80°C, dried for 5 hours, and then taken out, cut into small discs with a diameter of 12 mm, and then placed in a vacuum drying oven at 100°C, dried overnight for about 12 hours, and then taken out to obtain The final electrode piece was weighed and placed in a glove box with an argon atmosphere for standby use. The water and oxygen contents in the glove box were both less than 1ppm. A CR2025 button battery mold was selected to prepare the electrode piece as the positive electrode and the lithium sheet as the negative electrode. GR-FH001 electrolyte and polyethylene diaphragm were selected to assemble the diaphragm and shrapnel into a complete CR2025 button half-cell. The battery was transferred to an air-conditioned room at 25°C and left to stand for 4 to 24 hours. The electrochemical performance was tested with a Xinwei battery device, and the working voltage was set to 2.8 to 4.3V.

[0043] The electrochemical performance of the positive electrode material in this embodiment was tested at 0.5C. The first charge and discharge curve is as follows: Figure 4 As shown, the cycle performance curve is as follows Figure 5 As shown in the figure, the battery prepared in this embodiment has a discharge capacity of up to 181.0 mAh g during the charge and discharge process at a rate of 0.5 C. -1 After 100 cycles, the battery capacity retention rate is 86.4%, which has good cycle stability. The working voltage is increased, and the cycle performance is tested at a rate of 0.5C in the voltage range of 2.8 to 4.5V. The results are as follows Figure 6 As shown in the figure, it can also work stably at a higher voltage and has a higher discharge capacity, reaching 191.8 mAh g -1 After 100 cycles, the capacity retention rate is 78.1%, which is almost the same as the discharge specific capacity after 100 cycles at a voltage of 4.3V, indicating that the material is capable of charge and discharge cycles at a high cut-off voltage of 2.8 to 4.5V and exhibits excellent cycle stability.

[0044] Furthermore, the present invention also provides a comparative example, the preparation process of which is different from that of Example 1 in that: S1. Accurately weigh the following raw and auxiliary materials using an electronic analytical balance: lithium hydroxide, [Ni 0.86±x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2] precursor (typical composition is [Ni 0.86 Co 0.04 Mn 0.1(OH)2]), wherein the molar ratio of LiOH: precursor is 1.05:1.0; based on the same preparation process as Example 1, the positive electrode material prepared in the comparative example still has a single crystal morphology, but is not high-entropy doped.

[0045] The positive electrode materials in the comparative example were assembled into the same button-type half-cell, and the electrochemical performance test was carried out at 0.5C. The battery prepared in the comparative example had a discharge capacity of 185.3 mAh g during the charge and discharge process at a rate of 0.5C. -1 After the battery has been cycled for 100 cycles, the capacity retention rate of the battery is 66.2%, and the cycle stability is significantly worse than that of the high-entropy high-nickel single crystal lithium-ion battery positive electrode material in Example 1; the charging cut-off working voltage is increased, and the cycle performance is tested at a rate of 0.5C in the voltage range of 2.8 to 4.5V. The capacity retention rate of the positive electrode material in the comparative example after 100 cycles is only 54.3%, which is much lower than the capacity retention rate of 78.1% of the high-entropy high-nickel single crystal lithium-ion battery positive electrode material in Example 1. It can be seen that the high-entropy high-nickel single crystal lithium-ion battery positive electrode material in Example 1 is more capable of working under a high cut-off voltage of 2.8 to 4.5V, and exhibits excellent cycle stability.

[0046] Example 2

[0047] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S1, gallium oxide is replaced with an equal molar amount of indium oxide; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0048] Example 3

[0049] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S1, aluminum oxide is replaced with an equal molar amount of lanthanum oxide; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0050] Example 4

[0051] This embodiment provides a high entropy high nickel single crystal lithium ion battery positive electrode material, and its preparation method is the same as that of embodiment 1, the only difference is that in step S1, LiOH: precursor: Al 3+ :Ga 2+ :Ti 4+ : Y 3+ :Zr 4+ The molar ratio is 1.08:0.97:0.01:0.005:0.005:0.005:0.005; after electrochemical performance testing, this embodiment has similar beneficial effects to embodiment 1.

[0052] Example 5

[0053] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S4, the heating rate of the tubular furnace is 2°C / min; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0054] Example 6

[0055] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S4, the sintering temperature is 750°C; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0056] Example 7

[0057] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S4, the sintering temperature is 850°C; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0058] Example 8

[0059] This embodiment provides a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material, and its preparation method is the same as that of Example 1, with the only difference being that in step S4, the insulation time is 15 hours; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0060] Example 9

[0061] This embodiment provides a high entropy high nickel single crystal lithium ion battery positive electrode material, and its preparation method is the same as that of embodiment 1, the only difference is: the expression Li 1+δ [Ni 0.86±x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2] 1-z M z In O2, z=0.09, in step S1, M=[Al+Ga+Ti+Y+Zr+Mg+Nb+B+Si], and the molar ratio of Al:Ga:Ti:Y:Zr:Mg:Nb:B:Si=2:1:1:1:1:1:1:0.5:0.5; after electrochemical performance testing, this embodiment has similar beneficial effects to Example 1.

[0062] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A high entropy high nickel single crystal lithium ion battery positive electrode material, characterized in that: The lithium-ion battery positive electrode material is a single crystal morphology, and the molecular expression is: Li 1+δ [Ni 0.86±x Co 0.04±x / 2 Mr 0.1±x / 2 (OH)2] 1-z M z O2, Among them, 0≤δ≤0.2, 0≤x≤0.06, 0.005≤z≤0.25; M is at least five of Al, Mg, Ti, Zr, Ga, In, Y, La, B, Si, and Nb.

2. The high entropy high nickel single crystal lithium ion battery positive electrode material according to claim 1, characterized in that: M=[Al+Ga+Ti+Y+Zr], [Al+In+Ti+Y+Zr], [La+Ga+Ti+Y+Zr] or [La+In+Ti+Y+Zr], and the molar ratio of (Al or La):(Ga or In):Ti:Y:Zr is 2:1:1:1:

1.

3. The method for preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material according to claim 1, characterized in that: The following steps are involved: S1. Grind the lithium source (lithium hydroxide) and mix it with the precursor and the doping material to obtain a mixed raw material; S2. The mixed raw material is placed in a tubular furnace, heated to 450 ℃ ~ 600 ℃ at a heating rate of 2 to 5 ℃ / min in an oxygen atmosphere, and kept warm for 4 to 8 hours to obtain a pre-sintered material after pre-sintering; S3. The pre-burned material is crushed and ground evenly to obtain a pre-burned powder; S4. Place the pre-burned powder in a tubular furnace, heat it to 750°C to 950°C at a heating rate of 2 to 5°C / min in an oxygen atmosphere, and keep it warm for 12 to 24 hours. After sintering, a high-entropy, high-nickel single crystal lithium-ion battery positive electrode material is obtained.

4. The method for preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material according to claim 3, characterized in that: In step S1, the molar ratio of lithium hydroxide, precursor, and doping material is: (1+δ):(1-z):z, 0≤δ≤0.2, 0.005≤z≤0.

25.

5. The method for preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material according to claim 3, characterized in that: In step S1, the precursor material uses an 8-series ternary precursor, and the chemical formula is: Ni 0.86±x Co 0.04±x / 2 Mn 0.1±x / 2 (OH)2, 0≤x≤0.

06.

6. The method for preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material according to claim 3, characterized in that: In step S1, the doping material is at least five oxides or hydroxides of Al, Mg, Ti, Zr, Ga, In, Y, La, B, Si, and Nb.

7. The method for preparing a high-entropy high-nickel single crystal lithium-ion battery positive electrode material according to claim 6, characterized in that: The specific combination of doping materials is [Al+Ga+Ti+Y+Zr], [Al+In+Ti+Y+Zr], [La+Ga+Ti+Y+Zr] or [La+In+Ti+Y+Zr], and the molar ratio of (Al or La):(Ga or In):Ti:Y:Zr is 2:1:1:1:1.

Citation Information

Patent Citations

  • Modified ternary cathode material and preparation method thereof

    CN109755484A

  • High-entropy solid solution positive electrode material and preparation method and application thereof

    CN113851641A

  • Method for preparing lithium battery positive electrode material with high-configuration entropy surface layer by solid-liquid phase method

    CN116404153A

  • High-entropy strategy sodium ion battery layered positive electrode material, preparation method and application

    CN117352717A

  • High-entropy doped layered lithium-rich manganese-based positive electrode material and preparation method thereof

    CN117712339A

Cited By

  • Preparation method of high-oxidation-state element high-entropy doped high-nickel layered positive electrode material

    CN120199811A